First step results from a phase II study of a dendritic cell vaccine in glioblastoma patients (CombiG-vax) - Ridolfi, Laura; Gurrieri, Lorena; Riva, Nada; Bulgarelli, Jenny; De Rosa, Francesco; Guidoboni, Massimo; Fausti, Valentina; Ranallo, Nicoletta; Calpona, Sebastiano; Tazzari, Marcella; Petrini, Massimiliano; Granato, Anna Maria; et al. (Frontiers in Immunology, 2024)
Background. Glioblastoma (GBM) is a poor prognosis grade 4 glioma. After surgical resection, the standard therapy consists of concurrent radiotherapy (RT) and temozolomide (TMZ) followed by TMZ alone. Our previous data on melanoma patients showed that Dendritic Cell vaccination (DCvax) could increase the amount of intratumoral-activated cytotoxic T lymphocytes Methods. This is a single-arm, monocentric, phase II trial in two steps according to Simon's design. The trial aims to evaluate progression-free survival (PFS) at three months and the safety of a DCvax integrated with standard therapy in resected GBM patients. DCvax administration begins after completion of RT-CTwith weekly administrations for 4 weeks, then is alternated monthly with TMZ cycles. The primary endpoints are PFS at three months and safety. One of the secondary objectives is to evaluate the immune response both in vitro and in vivo (DTH skin test). Results. By December 2022, the first pre-planned step of the study was concluded with the enrollment, treatment and follow up of 9 evaluable patients. Two patients had progressed within three months after leukapheresis, but none had experienced DCvax-related G3-4 toxicities Five patients experienced a positive DTH test towards KLH and one of these also towards autologous tumor homogenate. The median PFS from leukapheresis was 11.3 months and 12.2 months from surgery. Conclusions. This combination therapy is well-tolerated, and the two endpoints required for the first step have been achieved. Therefore, the study will proceed to enroll the remaining 19 patients. (Eudract number: 2020-003755-15